ECONOMIC ASPECTS OF LEGAL SUPPORT FOR EMPLOYMENT IN UZBEKISTAN - Shayusupova Lobar Rikhsievna; Khasanov Azizjon Akhrol Ugli (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This study examines the employment sector in Uzbekistan within the framework of the country's new development strategy for 2022-2026, focusing on job creation, social protection, and legislative enhancements. Drawing upon legislative frameworks such as the laws "On Employment" and "On Private Employment Agency," and recent enactments including the Labor Code and the Law on External Labor Migration, the study investigates the modernization efforts within Uzbekistan's labor market. Additionally, the study explores the impact of minimum wages on employment through a meta-analysis of data from emerging economies, providing insights into the employment dynamics in Uzbekistan. Through the analysis of Presidential Decree No. UP-5052, measures to fortify workforce rights and enhance employment-related activities are scrutinized, offering a comprehensive overview of Uzbekistan's endeavors to advance its labor sector.